Superovulatory response and embryo recovery in Frieswal Cows using FSH & PMSG - MATHUR, A K; KUMAR, P SENTHIL (The Indian Journal of Animal Reproduction, 2023)
The studies were conducted on 15 Frieswal cows maintained under normal managemental conditions at MF, Meerut (UP). The animals were divided into two groups. Group I had 7 animals where as 8 animals were kept in group II. Group I animals were superovulated using PMSG @ 1500 JU at I 0th day of cycle and Group II animals with 400 mg ofFSH in multiple doses at 9th to 12th day of the estrous cycle. It was observed that 57.2% animals did not respond the superovulatory treatment in PMSG treated group as compared to 25% in FSH treated group. The superovulatory response in the animals responded to the treatment in terms of number of corpus luteum (CL) present on day 617th after the onset of oestrus was 7.67± 1.34 and 11.33± l .85 in group l &II, respectively. The mean embryo recovered was similar in both the groups ( 4.3±0.67 & 4.2±0.40). The quality evaluation of embryo revealed that the mean no. of embryo under the category of good, fair and poor were 2.0, 1.67, 0.67 and 2.16, 1.5 & 0.67 in group I and II, respectively.